43rd Fluid Dynamics Conference 2013
DOI: 10.2514/6.2013-2968
|View full text |Cite
|
Sign up to set email alerts
|

Control of a canonical separated flow

Abstract: A stalled airfoil can exhibit up to three natural frequencies associated with the separated flow: that of the shear layer, the separation bubble, and the wake. This work investigates these flow phenomena using a simplified canonical setup and targets their frequencies with zero-net mass-flux (ZNMF) actuation in order to effectively and efficiently reduce the extent of the separation. First, boundary layer separation is created on a flat plate model, devoid of curvature that would otherwise include effects part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
(15 reference statements)
2
13
0
Order By: Relevance
“…We note that TDMD identifies a mode at 49Hz, while standard DMD identifies a similarly shaped mode at 58Hz. Local hot-wire measurements on the same flow configuration, previously reported in [40,39], corroborate the presence of a frequency peak in the range 45Hz-50Hz, as identified by TDMD. In Figure 4, the real components of the dominant oscillatory vorticity modes-computed as the curl of DMD/TDMD velocity modes-are plotted.…”
Section: Dmd On Flow Separation Experimentssupporting
confidence: 81%
See 1 more Smart Citation
“…We note that TDMD identifies a mode at 49Hz, while standard DMD identifies a similarly shaped mode at 58Hz. Local hot-wire measurements on the same flow configuration, previously reported in [40,39], corroborate the presence of a frequency peak in the range 45Hz-50Hz, as identified by TDMD. In Figure 4, the real components of the dominant oscillatory vorticity modes-computed as the curl of DMD/TDMD velocity modes-are plotted.…”
Section: Dmd On Flow Separation Experimentssupporting
confidence: 81%
“…As such, we now consider an experiment of separated flow over a flat plate (Re=10 5 with respect to chord length), with snapshots of the velocity field (n = 42 976, m = 3 000) measured using timeresolved particle image velocimetry (TR-PIV) in a wind tunnel sampled at a rate of f s = 1600Hz (δt = 0.625ms). Further details of the experimental setup can be found in [39]. DMD and TDMD are performed using a rankreduction level r = 25, which corresponds to retaining over 99% of energy content based on an SVD of X.…”
Section: Dmd On Flow Separation Experimentsmentioning
confidence: 99%
“…Several studies have shown that effective separation control strategies exploit the most amplified frequency of the shear-layer instability. [9][10][11][12][13]22 Since the dynamical characteristics of the separated flow (including the modality of the vortex generation due to the Kelvin-Helmholtz instability) are identified by the surface pressure measurements, the pressure array DMD results may be viable for state estimation in closed loop control of the separated flow. To illustrate how this can be implemented to provide dynamical characteristics on the fly, online DMD is performed for the surface microphone measurements of the baseline separated flow with the weighting factor λ set to 0.996.…”
Section: Unsteady Surface Pressure Dmdmentioning
confidence: 99%
“…Irrespective of the form of actuation, several studies have shown that efficient control is achieved for forcing frequencies near the frequency of the shear layer instability. [9][10][11][12] Recently, Griffin et al 13 provide results of varying the actuation frequency of a ZNMF jet in the vicinity of the characteristic frequencies of a canonical separated flow. The authors find that forcing near the shear layer frequency has the most dramatic impact on reducing separation.…”
Section: Introductionmentioning
confidence: 99%
“…Sketch of the canonical separated flow experiment setup (adapted from[10]) and the PIV measurement region.…”
mentioning
confidence: 99%